Mathematics Literacy of Middle School Students with Socio-Cultural Context Viewed from Learning Style - Fernanda, Betita Nadia; Shodikin, Ali; Susanah, Susanah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
The capacity to comprehend, reason, create, recognize, and compute to solve any mathematical problem about day-to-day living is known as mathematical literacy. Learning style is each individual's method of receiving and understanding all the information they get. One aspect that influences students' mathematical literacy is the learning style aspect. This research goal is to find out how junior high school students' mathematical literacy relates to the socio-cultural context in terms of learning styles. This research uses a qualitative method with a descriptive approach. This research involved three students in class eight at SMP Negeri 1 Perak with different learning styles with equal abilities as subjects. The results of this research indicate that student’s learning styles influence students' mathematical literacy processes. The mathematical literacy of students who have an auditory learning style is better than the mathematical literacy of students who have a visual and kinesthetic learning style. Students' mathematical literacy has not been achieved using existing indicators.